Cassanova Color Guard Community Logo Design - Mirrah Fitriana Maghfiroh (International Journal of Seocology, 2022)
The role of the color guard in a marching band is as a dancer who accentuates the collaboration between gestures and acrobatic games using color guard instruments such as flags, rifles, and sabers. Initially, the color guards always appeared together in a marching band team. However, along with the current developments, color guards can appear separately without having to be with the marching band team. One of the groups formed was Cassanova Color Guard from the Special Region of Yogyakarta. Cassanova Color Guard formed on 3th June 2010 consist of 7 color guard marching band members in Yogyakarta. Cassanova has made guest appearances and entered competitions but does not have a logo yet. Cassanova decided to create a logo to show its existence to the public. In making the logo, research carried out used descriptive qualitative methods with data collection techniques through observation and interviews with stakeholders. Then an agreement was found that Cassanova's logo consisted of a picture of the Tugu Jogja showing origins from Yogyakarta, seven colors of the rainbow indicating that it consisted of 7 marching band units, the Sirius star with the hope that it would continue to exist and shine, Cassanova's writing in gold with the hope that it would continue to excel and celebrate success, and inscription color guard shows that this group is a color guard community.